Trust and Cheating. (12th January 2016) - Butler, Jeff; Giuliano, Paola; Guiso, Luigi
Abstract : When we take a taxi we may feel cheated if the driver takes an unnecessarily long route despite the lack of a contract to take the shortest possible path. Is the behaviour of the driver affected by beliefs about our cheating notions? We address this question in the context of a trust game. We find that both parties to a trust exchange have personal notions of cheating and that these notions have a bimodal distribution. We conceptualise cheating notions as moral expectations, which provide a micro‐foundation for guilt. Cheating notions substantially affect decisions on both sides of the trust exchange.